Improvement Effort of Online Statement of Police Report Services by the Intelligence and Security Unit at Tegal Resort Police (Advances in Police Science Research Journal, 2024)
This research is based on innovation from the Indonesian National Police in providing services to the community in the form of administrative services in the form of online Police Record Certificates (SKCK). However, this online SKCK service is still not the main choice of the community in the process of making SKCK. Therefore, this study aims to find out how management is implemented in online SKCK services and how efforts to improve online SKCK services at Tegal Resort Police are carried out by SatIntelkam. This study uses the concept of improvement efforts, the concept of public service, the concept of online SKCK services, and the concept of Intelligence and Security. As for the theory, management theory and organizational resource theory are used as analytical tools. The approach used in this study is a qualitative approach and the type of research is descriptive research. The data sources used are primary data sources such as interviews, and secondary data sources in the form of documents. Data collection techniques used in this study are observation, interviews, and document review. Data analysis techniques used are data collection, data reduction, data presentation and conclusion. The research that has been carried out produces findings in the form of a very distant comparison between very high manual SKCK applicants and very few online SKCK applicants. The inhibiting factors for the implementation of this service were caused by internal factors, namely online SKCK service implementing officers who did not yet have the competence for online SKCK services, personnel who had not received implementing fees, and many online SKCK devices that were damaged. External factors in the form of many people who do not know about SKCK online. Improvement efforts that have been made are socialization through social media and SKCK on the spot. The advice given by the author here is to overcome the inhibiting factors and the implementation of outreach to the community is further enhanced so that people can use this online SKCK service.
Keywords: Upaya Peningkatan, SKCK online, Satuan Intelkam Polres Tegal